Computational simulation of critical speed and dynamic analysis of agglomerated CNTs/fiber/polymer/metal laminates rotating cylindrical shell - Rahmad Syah (Arabian Journal of Chemistry, 2021)
The main object of this research is to consider the effects of agglomeration on the free vibration and critical speed of rotating carbon nanotubes (CNTs)/fiber/polymer/metal laminates (CNTFPMLs) thin cylindrical shells. The strain–displacement relations are obtained using Love’s first approximation shell theory, and moduli of carbon nanotubes reinforced composites (CNTRCs) cylindrical shells are derived using Eshelby-Mori-Tanaka. Furthermore, fibers are reinforced by means of extended rule of mixture. There are four phases for generating CNTFPMLs cylindrical shell which are fiber, CNTs, polymer matrix and metal. In this work, the effects of several items on vibration of agglomerated CNTFPMLs rotating cylindrical shells are considered, namely, material properties of the fiber phase, lay-ups, volume fractions of metal and composite sections, rotational speed and agglomeration constants. The results demonstrated that the non-dimensional frequencies of symmetric agglomerated CNTs were greater than asymmetric for μ=0 and μ=1, while they were smaller for μ=0.5. In addition, although the cylindrical shell reaches the critical speed for symmetric and asymmetric agglomerated CNTs with glass fiber (at μ=0 and μ=1), respectively, the non-dimensional frequencies of none of the cylindrical shells reach the critical speed and their forward directions are changed before reaching the critical speed for μ=0.5.